Correlation of Road Safety Criteria with Occupant Safety Criteria in Impacts on Crash Cushions - Ernst Tomasch; Gregor Gstrein (Infrastructures, 2024)
Road restraint systems are used to protect vehicle occupants if the vehicle runs off the road and potentially collides with a dangerous obstacle. These road restraint systems must successfully pass the tests defined in EN 1317, or the Manual for Assessing Safety Hardware (MASH) before they are allowed to be installed. The safety assessment is carried out according to the criteria of ASI (Acceleration Severity Index), THIV (Theoretical Head Impact Velocity), OIV (Occupant Impact Velocity), ORA (Occupant Ridedown Acceleration), and PHD (Post-Impact Head Deceleration). Usually very old vehicles are used for these tests, and there is no assessment of occupant criteria such as HIC (Head Injury Criteria), chest deflection, etc. The objective of the study was to compare the occupant safety of vehicles that are commonly used in EN 1317 with vehicles that have improved safety equipment. Test results from two different vehicles (a commonly used vehicle in EN 1317 and a vehicle with improved safety equipment) and two different impact conditions (full overlap and an overlap of 50%) were compared. Measurement data from a Hybrid HIII 50th percentile anthropomorphic test device (ATD) (Denton ATD, INC.) was recorded during the tests to assess occupant safety. The tests have shown that vehicles with improved safety equipment perform better than vehicles that are commonly used in EN 1317-3 tests. The values for the occupant safety criteria assessed were well below the Euro NCAP (New Car Assessment Programme) or Federal Motor Vehicle Safety Standard (FMVSS) limits. However, the limits of the road safety criteria were in some cases considerably exceeded regardless of the vehicle. This has been observed in particular for the offset impact condition. THIV and OIV were supposed to be able to assess the risk of head injuries. However, these two criteria correlated negatively with the head criteria, HIC or a3ms. However, a positive correlation was found for the ASI with the HIC and the a3ms head acceleration. Even if some of the criteria for road safety correlate with the criteria for occupant safety, it is doubtful whether the criteria for road safety are suitable for assessing the risk of injury to vehicle occupants.